2015
DOI: 10.1371/journal.pgen.1005155
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease Associated Transcription Factor TCF21 Regulates Smooth Muscle Precursor Cells That Contribute to the Fibrous Cap

Abstract: Recent genome wide association studies have identified a number of genes that contribute to the risk for coronary heart disease. One such gene, TCF21, encodes a basic-helix-loop-helix transcription factor believed to serve a critical role in the development of epicardial progenitor cells that give rise to coronary artery smooth muscle cells (SMC) and cardiac fibroblasts. Using reporter gene and immunolocalization studies with mouse and human tissues we have found that vascular TCF21 expression in the adult is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 54 publications
1
108
0
Order By: Relevance
“…More recently, epicardial derived fibroblasts, as traced with Wt1 CreERT2 or Tbx18 CreERT2 alleles, were shown to give rise to 80% or more of the total fibroblasts in the left ventricle of a failing mouse heart1131 Thus, there is strong support for the conclusion that tissue-resident fibroblasts in the adult heart are the primary cell type that generates myofibroblasts upon injury. This same paradigm appears to be present in the fibrotic cap of diseased vasculature in atherosclerotic mice where Tcf21 lineage-traced cells were shown to uniformly express αSMA, periostin and PDGFRα41.…”
Section: Disscussionmentioning
confidence: 75%
“…More recently, epicardial derived fibroblasts, as traced with Wt1 CreERT2 or Tbx18 CreERT2 alleles, were shown to give rise to 80% or more of the total fibroblasts in the left ventricle of a failing mouse heart1131 Thus, there is strong support for the conclusion that tissue-resident fibroblasts in the adult heart are the primary cell type that generates myofibroblasts upon injury. This same paradigm appears to be present in the fibrotic cap of diseased vasculature in atherosclerotic mice where Tcf21 lineage-traced cells were shown to uniformly express αSMA, periostin and PDGFRα41.…”
Section: Disscussionmentioning
confidence: 75%
“…The same group demonstrated that TCF21 regulates the development of the epicardial progenitor cells that give risk to smooth muscle cells that contribute to the fibrous cap. 140 Similar approaches have provided new insight into the roles of PHACTR1 141 and ADAMTS7 142 in atherosclerosis. ADAMTS7 plays a role in the regulation of vascular smooth muscle cell migration, and Bauer et al 143 recently demonstrated that Adamsts7 −/− mice were protected from atherosclerosis on an Ldlr −/− or Apoe −/− background and showed reduced neointimal formation after femoral wire injury and that Adamsts7 −/− vascular smooth muscle cells showed reduced migration in the setting of tumor necrosis factor-α stimulation, consistent with a proatherogenic effect of ADAMTS7.…”
Section: From Locus To Functionmentioning
confidence: 99%
“…A tool for identifying Tcf21 lineage cells was generated by inserting an inducible Cre recombinase at the Tcf21 locus 118 ( Tcf21 mCrem ). Tcf21 lineage cells were present in the adventitia of coronary arteries and the aortic root, as well as aortic root media and fibrous cap after injury 102, 115 . In addition to cells of the heart, adult induction of Tcf21 mCrem recombination also lineage tags splenic interstitial cells 119 , kidney podocytes and mesangial cells, lung interstitial cells, and liver interstitial cells 8, 118 .…”
Section: Genetic Tools Used To Identify Adventitial Fibroblastsmentioning
confidence: 99%
“…Tcf21 LacZ reporter mice 114 have expression of β-galactosidase in coronary adventitia, aortic root, and interstitial cells of the heart 115 . In atherosclerotic lesions, β-galactosidase activity was observed on the luminal side of lesions and in the fibrous cap 115 . In the kidney, another Tcf21 LacZ 116 reporter line showed β-galactosidase activity in adventitial cells 117 .…”
Section: Genetic Tools Used To Identify Adventitial Fibroblastsmentioning
confidence: 99%